ANALISA MASTER PIN EXCAVATOR HITACHI EX1900 - 6 - , DIMAS PRIYANTO; , Lilik Dwi Setyana, S.T., M.T. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Master pin is one of important component in the undercarriege of excavator, it is combine with bushing used to connect and disconnect the track link assy. Track link is used as a footstool of track roller and chassis, sprocket teeth while spinning will play the track link and turn it into a rolling motion, so that allowing the unit to run. If the master pin is damage (broken) under it lifetime, the study aims of material must do to help to search the cause of damage. This study aims to known the type of material used in the excavator Hitachi EX1900-6 master pin, to known the structure that occurs in the master pin, and to determine the mechanical and physical properties of the master pin. Testing was conducted on the testing of chemical composition, microstructure, hardness, and tensile test. Results showed that the excavator Hitachi EX1900 - 6 master pin material is low alloy Steel AISI-SAE Steel 4340. Existing structure of the specimen is dominated by ferrite and pearlite, showing the master pin has a hard and ductile. Master pin has a maximum stress of 93.31 kg/mm2, the maximum strain of 7.5% and has a value hardness of 268.699 VHN (25.1 HRC). And the master pin has undergone a process of normallizing but the surface layer of master pin is more malleable than that inner so more easily to worn-out.